Surgical results of sacral perineural (Tarlov) cysts - Tanaka, Masato; Nakahara, Shinnosuke; Ito, Yasuo; Nakanishi, Kazuo; Sugimoto, Yoshihisa; Ikuma, Hisanori; Ozaki, Toshifumi (Acta medica Okayama, 2006)
The purpose of this study was to investigate the surgical outcomes and to determine indicators of the necessity of surgical intervention. Twelve consecutive patients harboring symptomatic sacral perineural cysts were treated between 1995 and 2003. All patients were assessed for neurological deficits and pain by neurological examination. Magnetic resonance of imaging, computerized tomography, and myelography were performed to detect signs of delayed filling of the cysts. We performed a release of the valve and imbrication of the sacral cysts with laminectomies in 8 cases or recapping laminectomies in 4 cases. After surgery, symptoms improved in 10 (83%) of 12 patients, with an average follow-up of 27 months. Ten patients had sacral perineural cysts with signs of positive filling defect. Two (17%) of 12 patients experienced no significant improvement. In one of these patients, the filling defect was negative. In conclusion, a positive filling defect may become an indicator of good treatment outcomes.